The Fibroblast Growth Factor 9 (Fgf9) Participates in Palatogenesis by Promoting Palatal Growth and Elevation - Li, Ruomei; Sun, Yidan; Chen, Zhengxi; Zheng, Mengting; Shan, Yuhua; Ying, Xiyu; Weng, Mengjia; Chen, Zhenqi (Frontiers in Physiology, 2021)
Cleft palate, a common global congenital malformation, occurs due to disturbances in palatal growth, elevation, contact, and fusion during palatogenesis. The Fibroblast growth factor 9 (FGF9) mutation has been discovered in humans with cleft lip and palate. Fgf9 is expressed in both the epithelium and mesenchyme, with temporospatial diversity during palatogenesis. However, the specific role of Fgf9 in palatogenesis has not been extensively discussed. Herein, we used Ddx4-Cre mice to generate an Fgf9–/– mouse model (with an Fgf9 exon 2 deletion) that exhibited a craniofacial syndrome involving a cleft palate and deficient mandibular size with 100% penetrance. A smaller palatal shelf size, delayed palatal elevation, and contact failure were investigated to be the intrinsic causes for cleft palate. Hyaluronic acid accumulation in the extracellular matrix (ECM) sharply decreased, while the cell density correspondingly increased in Fgf9–/– mice. Additionally, significant decreases in cell proliferation were discovered in not only the palatal epithelium and mesenchyme, but also among cells in Meckel’s cartilage and around the mandibular bone in Fgf9–/– mice. Serial sections of embryonic heads dissected at embryonic day 14.5 (E14.5) were subjected to craniofacial morphometric measurement. This highlighted the reduced oral volume owing to abnormal tongue size and descent, and insufficient mandibular size, which disturbed palatal elevation in Fgf9–/– mice. These results indicate that Fgf9 facilitates palatal growth and timely elevation by regulating cell proliferation and hyaluronic acid accumulation. Moreover, Fgf9 ensures that the palatal elevation process has adequate space by influencing tongue descent, tongue morphology, and mandibular growth.